Alcohol Use Among Youth in Student Dormitories - Matović, Milica; Žunić-Pavlović, Vesna (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
The aim of this paper is to examine the prevalence and characteristics of alcohol use among students in student dormitories. The sample contains 223 students of the University of Belgrade, aged 19–30, who lived in student dormitories during the research. The questionnaire of the Core Institute was used for this research. The results of this study show that one-fifth of students in student dormitories consume alcohol four or more times a week, while in the past two weeks, 40% of students have consumed five or more drinks on one occasion. Most students have positive attitudes toward alcohol use, despite the fact that they have experienced negative consequences of drinking. The final analysis showed that the use of alcohol among students in student dormitories is associated with some study characteristics and socio-demographic characteristics of the students.